Historical evolution of sex and age estimation techniques through the skull - de Carvalho, Naiá Taís Magalhães (Revista Sistemática, 2024)
The estimation of sex and age through cranial measurements is a fundamental practice in various fields such as physical anthropology, archaeology, and forensic medicine. Over the centuries, techniques and methodologies have been developed and refined to increase the accuracy of these estimates, reflecting advances in anatomical knowledge, imaging technology, and statistical analysis. This article aims to explore the historical evolution of these techniques, highlighting the major changes and innovations from the rudimentary methods used in early anthropological investigations to the sophisticated contemporary approaches incorporating cutting-edge technologies like computed tomography and machine learning algorithms. In addition to reviewing traditional methods, this study examines how the application of new technologies has contributed to greater accuracy and reliability in sex and age estimations, as well as the implications of these improvements for population studies and forensic investigations. By tracing this evolution, it seeks not only to provide a comprehensive overview of the historical development of these techniques but also to contextualize future trends and the challenges that still need to be addressed.